Analysis On The Relationship Of Extrovert-Introvert Personality And Students’ Speaking Performance In English Study Program Of Halu Oleo University - Samand, Sri Muniarty; Sailan, Zalili; Lio, Asrun (Halu Oleo University, 2019)
Speaking is one of the productive skills in English competence which can help us to interact with other people. However, in a class, not all the students can make equal improvement in speaking skill even though they get the same treatment from the teacher. It happens because there are many factors that influence students’ speaking performance. One of the factors is affective factor that can be from students’ personality. In this category, personality can be classified into two types, they are extrovert and introvert. This present study investigates the correlation between extrovert personality and introvert personality and students’ speaking performance at the students in English Study Program of Halu Oleo University in the fourth semester. Total 35 students were selected as the sample and their personality type was determined by using Mark Parkinson Personality Questionnaire and their speaking score from the speaking test. The objective of the study is to examine, whether there is correlation between extrovert-introvert personality and students’ speaking performance or not and also to know which personalities have better achievement in speaking performance. This study applied descriptive quantitative design. The personality and the students score were correlated by using Pearson Product Moment Correlation. The result of correlation testing reveals that there is no significant correlation between extrovert personality and speaking performance (0,575 > 0,05) and also there is no correlation between introvert personality and speaking performance (0,505 > 0,05). Then, other result shows that introvert students have better achievement in speaking than extrovert students, which means score of introvert is 77,56 while mean score of extrovert is 75,56.